The Reception Analysis in Ernest Hemingway’s Hills Like White Elephants - Andi Sarwindah; Abidin Pammu; Andi Inayah Soraya (Hasanuddin University, 2024)
This study is aimed to know the reader response toward “Hills Like White Elephants” by Ernest Hemingway. To limit the scope of the study, the analysis focused on reader’s response consist of intellectual aspect and emotional aspect and also moral value toward this short story. The readers are 20 students from English Department, Faculty of Cultural Sciences, Hasanuddin University. The method used is descriptive quantitative. Readers are given the opportunity to read Ernest’s short story, then answer a questionnaire consisting of agree and disagree question about the idea and emotions after reading the story itself. There are 20 respondents from English Department students, Faculty of Cultural Sciences, Hasanuddin University. The results of this study indicate that, in responding to Hills Like White Elephants short stories, readers can respond from two aspects namely, intellectual and emotional aspect, each of which consists of five aspects. Reader's response to short stories has differences both in terms of intellectual and emotional. The most positive response in intellectual are languange 90%, and the most negative response in intellectual aspect are theme 45%. In the other hand the most positive response in emotional aspect are emotion 75% and interest 75%. There are some moral value describes by readers including, thinking before acting, loving yourself, respecting others, life is a choice, a mother's love for all time, and honesty.